OBSERVATION OF A MAGNETIC TRANSITION IN PARA-PYRIDYL NITRONYL NITROXIDE USING ZERO-FIELD MU-SR - Blundell, S; Pattenden, P; Valladares, R; Pratt, F; Sugano, T; Hayes, W (1994)
We report the observation of a magnetic transition at around 90 mK in the nitronyl nitroxide radical system para-pyridyl nitronyl nitroxide (p-PYNN) in zero applied field using the muon-spin rotation (μSR) technique. © 1994.